'Dancing in the mouth of the wolf': constructing the border through everyday life in socialist Albania. (January 2019) - Vullnetari, Julie
Abstract: Little is known about everyday life in socialist Albania, and even less about what were strategically sensitive and closed-off border areas. Through a historical geography of everyday life, this paper contributes to border studies by examining the multiplicity of border processes at different levels and for differently situated social actors. The paper also contributes to knowledge on 'actually existing' socialism, in particular in border zones along the (former) Iron Curtain, by setting out both the way in which the border was constituted materially, and how border spaces were experienced, lived and routinely practiced by local residents. The social and temporal reproduction of borders is shown to interlace state actors and local residents in intricate and often ambiguous ways. Evidence comes from oral history narratives of middle-aged and older Albanians who at the time of the research lived in villages bordering present-day Montenegro, Macedonia and Greece. The paper finds that dominant bordering frameworks imposed by the state were routinely challenged, reinterpreted and negotiated from below, producing a dynamic and multifaceted b/ordering process. Local residents complied with, but also resisted, the top-down statecraft of control and domination, constantly engaged in a balancing act that often seemed like 'dancing in the mouth of the wolf'. Highlights: Argues that everyday life is a powerful lens for understanding relations of power and resistance. Shows that constructing borders from top-down in communist Albania relied on fear. Demonstrates that Albanian citizens participated actively in the making of the border. Argues that borders as social constructs involve both politics and matters of emotions and affect.